Effects of Pollution and Contamination of Water Bodies: A Case of Anambra State - E. E., Enekwechi (African Journal of Education,Science and Technology (AJEST), 2017)
Pollution and contamination of both surface waters and groundwater regions within Anambra State have been in the increase. The effects of urbanization and infrastructural developments have resulted in high degree of pollution and contamination of various water regions in the state. Also erosion and indiscriminate dumping of refuse have exacerbated the problem of water pollution. This paper therefore undertakes a study of the physio-chemical and bacteriological qualities of some groundwater and surface water samples collected within the state. Laboratory analysis of the collected samples showed the presence of heavy metals and high E-coli values which indicate the evidence of faecal and non-faecal coliform counts. Fertilizers leached from farmlands by flood during rainfall and chemicals transported by flood from chemical factories may have contributed to high degree of both surface water bodies and groundwater regions. This paper suggests that government should enact and enforce legislations for management of industrial wastes to reduce the effect of chemical pollution of water bodies. There is also urgent need for government agencies to tackle the menace of erosion within the state as erosion is also a considerable source of pollution and contamination of water bodies within the state.